Encyclopedia of social theory - Ritzer, George (Gale virtual reference library, 2005)
Reference source for anyone interested in the roots of contemporary social theory. The encyclopedia examines the global landscape of all the key theories and the theorists behind them, presenting them in the context needed to understand their strengths and weaknesses.